Parental Awareness of Thalassemia Transmission and the Impact of Consanguineous Marriages: A Cross- Sectional Survey - Ali Muhammad Memon; Zulfiqar Ali Laghari; Jamshed Warsi; Ijaz, Farhat; Noman Sadiq; Rana Khurram Aftab (Journal of University College of Medicine and Dentistry, 2024)
Objective: To determine the frequency and relationship between consanguineous marriages and the awareness of thalassemia transmission among parents of thalassemic children. Methodology: A cross-sectional study was conducted from Oct 2019 to Feb 2020 in Hyderabad, Sindh, Pakistan. Three hundred and eleven thalassemic children families were included in the study using a convenient purposive sampling technique. After informed consent, the parents were interviewed and a proforma was filled out. Performa had questions about personal information, family information, and thalassemia awareness. Data was entered in SPSS version 21. Qualitative data was measured in frequencies. Results: Among Three hundred and eleven thalassemic families, 26.4% didn’t know consanguineous marriage causes thalassemia; 72.3% of participants weren’t tested for thalassemia; 98.7% didn’t consult a doctor before marriage; only 1 % of participants did prenatal genetic testing after pregnancy; 86.8% of the parents’ marriages were consanguineous. In 31.5% of these 311 children, the mother was her husband’s first cousin (daughter of spouse’s father’s sister). 16.4% of mothers were daughters of their spouse’s father’s brother, 15.8% of the spouse’s mother’s brother, and 23.5% of the spouse’s mother’s sister. Most couple who had thalassemic children don’t consult with a doctor nor do they go for genetic testing before marriage. Conclusion: Consanguineous marriage is common among parents having a thalassemic child. Urgent policies should be advised and implemented for the proper education of thalassemic families at the earliest.